Pemilihan Supplier Kursi dengan Metode Analytical Hierarchi Procces (AHP) dan Techniqe for Order Preference by Similary to Ideal Solution (TOPSIS) - Ahmad Khoiruddin Asrokhi; Gunawan Mohammad; Dwi Retna Sulistyawati (Jurnal Teknik dan Science, 2026)
This study aims to develop a decision support model for selecting the best upholstered trunk chair supplier at Khoiruddin Jati Furniture. The main issue faced by the company is that the supplier selection process is still carried out conventionally based on experience, personal relationships, and subjective managerial considerations, resulting in less measurable and inconsistent decisions. This condition may lead to unstable product quality, delivery delays, and inefficient production costs. To overcome these problems, this research integrates the **Analytical Hierarchy Process (AHP)** and the **Technique for Order Preference by Similarity to Ideal Solution (TOPSIS)** methods. The AHP method was applied to determine the priority weights of each criterion, while TOPSIS was used to rank supplier alternatives based on their closeness to the ideal solution. The evaluation criteria consisted of product quality, price, delivery punctuality, and warranty level, involving six supplier alternatives. The results of the AHP analysis indicated that the warranty level had the highest weight of 0.352, followed by price at 0.340, product quality at 0.202, and delivery punctuality at 0.106. The Consistency Ratio (CR) value of 0.07 indicated that the assessment was consistent and acceptable because it was below the required threshold of 0.1. Furthermore, the TOPSIS calculation showed that Supplier A achieved the highest preference value of 0.8499, followed by Supplier C with 0.6850, Supplier B with 0.5525, Supplier D and Supplier E with 0.4343, and Supplier F with 0.3599. Therefore, Supplier A was identified as the best supplier alternative because it had the closest performance to the ideal solution based on the AHP–TOPSIS analysis.